Effect of Farmers’ Behavior on Business Success Toward the Implementation of Partnership Patterns in Broiler Farming in Jawa Tengah - Zhafirah, Altaf; Suryantini, Any; Masyhuri, Masyhuri (Buletin Peternakan, 2024)
Overcome this challenge is by participating in partnerships. However, the implementation of the partnership pattern faces challenges, particularly indiscipline in complying with the agreed-upon rules between the farmer and the nucleus company. This lack of discipline can significantly affect the success of the broiler farming business. The success of a broiler farming business is determined by various factors related to the behavior of farmers, including their knowledge, attitudes, skills, motivation, and socio-economic conditions. To understand the effect of farmer behavior on the success of broiler farming, it is essential to study the implementation of partnership patterns. This research was conducted in Central Java Province, with a focus on Banyumas Regency and Klaten Regency. Respondents were selected using the snowball sampling technique, resulting in a sample size of 90 respondents. Data were analyzed both descriptively and quantitatively, and models were constructed using the Structural Equation Modeling (SEM-PLS) method. The findings revealed that (1) the implementation of the broiler farming business partnership pattern was categorized as very good; (2) the success level of the broiler farming business was categorized as very successful; and (3) attitudes, skills, motivation, and socio-economic conditions of farmers affect the success of broiler farming toward the implementation of partnership patterns. Farmers are advised to proactively propose to partner companies to focus on improving attitudes, skills, motivation, and socioeconomic conditions that have a positive effect on business success, involving training activities, technical development, and motivational support.